Linguistic spin in randomized controlled trials about age-related macular degeneration - Veldhuis, Nienke; Nuijts, Myrthe A.; Isphording, Luka; Lee-Kong, Felicia V. Y. L.; Imhof, Saskia M.; Stegeman, Inge (Frontiers in Epidemiology, 2022)
Objective: To evaluate the prevalence, type and extent of linguistic spin in randomized controlled trials (RCTs) exploring interventions in patients with age-related macular degeneration (AMD), as well as to investigate whether study variables were correlated with linguistic spin. Study design and setting: PubMed was searched from 2011 to 2020 to identify RCTs including patients with AMD. Two authors independently assessed a total of 96 RCTs. Linear regression analyses were performed to investigate whether linguistic spin was correlated with predefined study variables. Results: Linguistic spin was found in 61 of 96 abstracts (63.5%) and in 90 of 96 main texts (93.8%). Use of words pointing out the beneficial effect of a treatment and the use of ‘(statistically) significant/significance’ without reporting a P-value or a 95% confidence interval (CI) were the most frequently identified categories of linguistic spin. Sample size was significantly correlated with the total linguistic spin score (95% CI 0.38 – 5.23, P = .02). Conclusion: A high prevalence and extent of linguistic spin in RCTs about AMD was found. We highlighted the importance of objective reporting and awareness of linguistic spin among ophthalmologists and other readers.